2001
DOI: 10.1016/s0169-5983(01)00018-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic transition to turbulence in rigid abdominal aortic aneurysm models

Abstract: The hydrodynamic stability of cyclic ows inside rigid abdominal aortic aneurysm (AAA) models was investigated. Rectiÿed sine waveforms were used to simulate aortic ow conditions (Re mean = 1600-2100 and = 7:2-12.2). Depending on the bulge geometry (D=d and L=d ratios), AAA ows can be broadly classiÿed into three regimes, namely types A, B and C, respectively. While type A has no vortex formation, type B and C have distinctive laminar vortical structures that are very di erent from one another. The type of ow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Moreover, our results suggest that physical activity is harmful for a patient with an abdominal aortic aneurysm; the more-localized or well-developed aneurysms again being the most pathological. Yip & Yu (2001) and Salsac et al (2006) mention that during part of the cardiac cycle the flow in an aneurysm may become weakly turbulent. Since this repetitive occurrence of disturbed flow conditions seems especially harmful, we have investigated the hydrodynamic stability of pulsatile flows through a model aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results suggest that physical activity is harmful for a patient with an abdominal aortic aneurysm; the more-localized or well-developed aneurysms again being the most pathological. Yip & Yu (2001) and Salsac et al (2006) mention that during part of the cardiac cycle the flow in an aneurysm may become weakly turbulent. Since this repetitive occurrence of disturbed flow conditions seems especially harmful, we have investigated the hydrodynamic stability of pulsatile flows through a model aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…What has been established is that during part of the cardiac cycle the blood flow in the abdominal aorta becomes weakly turbulent during exercise, but it remains laminar during rest conditions (Les et al 2010). A local dilatation of the abdominal aorta may be expected to promote instability of the blood flow, and it is not unlikely that flashes of turbulence may occur during part of the cardiac cycle even during rest conditions (Yip & Yu 2001). This is believed to be beneficial, on the grounds that the presence of turbulence reduces the size of regions of flow stasis and the existence of a correlation between the presence of such regions and thrombus formation (Reininger et al 1994;Vorp et al 2001;Salsac et al 2004).…”
mentioning
confidence: 99%
“…Moreover, further experimental investigations by Yip and Yu [7] have shown that the onset of turbulence had actually taken place at the distal neck for a large AAA model (D/d =4) at the beginning of the deceleration phase of the ow cycle. Flow at the distal neck would remain turbulent for about two-fths of the decelerating phase.…”
Section: Introductionmentioning
confidence: 92%
“…Under pathological conditions, the peak Reynolds number may indicate local turbulence. Thus, more sophisticated simulation methods may be needed (Egelhoff et al, 1999;Yip et al, 2001). It should be noted that the significance of type II endoleak still remains controversial clinically.…”
Section: Article In Pressmentioning
confidence: 99%